Early-life famine exposure and subsequent risk of chronic diseases in later adulthood: a population-based retrospective cohort study - Zhao, Rui; Zheng, Qi; Chen, Le-qin (Frontiers in Public Health, 2025)
BackgroundOver the past few decades, China has experienced significant demographic and epidemiological changes. The sharp decline in fertility and mortality rates has accelerated population aging, contributing to an increase in the prevalence of chronic diseases. The nutritional condition during early life is associated with the onset of chronic illnesses later in adulthood. However, it remains unclear whether this association also increases the risk of multimorbidity in later adulthood.ObjectivesThis study aimed to systematically evaluate the association between early-life famine exposure and the subsequent development of 14 chronic diseases, as well as multimorbidity, and whether there exists a discrepancy in gender, residence, and famine severity.MethodsData are from the 2018 Wave 4 CHARLS database, a national survey covering 19,816 participants aged 45 years or older. Drawing from our past research on famine in China, we incorporated 3,867 participants, categorizing them into three groups based on their birth years. Considering that climate conditions and population density can influence the intensity of famine, we characterize its severity by establishing a threshold of 50% excess death rate. The 14 chronic diseases assessed by CHARLS were used as the main outcome indicator, with multimorbidity as a secondary outcome indicator. We conducted a stepwise logistic regression analysis to investigate the impact of exposure to famine in early life affects the development of chronic diseases in adulthood, presenting the findings as ORs and 95% CIs. Additionally, we assess multiple moderating factors such as gender, residence, and famine severity to evaluate the outcomes.ResultsOf the 3,867 participants included, the prevalence of each chronic disease ranged from 1.1% (Psychiatric disease) to 10.7% (Hypertension). Overall, 27.0% of participants reported being affected by at least one chronic disease, while 9.6% indicated they had suffered from two or more chronic conditions. Early-life exposure to famine makes it more likely to develop diabetes in later adulthood OR (95% CI) of 1.85 (1.26 to2.72), stroke OR (95% CI) of 1.96 (1.17 to 3.29), kidney disease OR (95% CI) of 1.91 (1.07 to 3.40), and multimorbidity OR (95% CI) of 1.39 (1.08 to 1.80), compared to those who did not face such conditions. The moderating effects analysis revealed that less severe famine exposure during toddlerhood was associated with an increased risk of multimorbidity in adulthood OR (95% CI) of 1.43 (1.01 to 2.03). Males exposed to famine during toddlerhood had a higher risk of multimorbidity in adulthood OR (95% CI) of 2.26 (1.29 to 3.98). Compared to the unexposed group, rural residents who experienced famine exposure in their early life are at a higher risk of developing multimorbidity by about 1.5 times in adulthood.ConclusionExperiencing famine in early childhood increases susceptibility to developing chronic diseases in later adulthood, with the risk of diabetes, stroke, and kidney disease nearly doubling. The association of multimorbidity in later adulthood varies according to the severity of the famine, gender, and residential area.